“It feels like I have a camera in my eye”: New methods for literacies research in maker-oriented classrooms - Hughes, Janette; Morrison, Laura; Robb, Jennifer A.; Hagerman, Michelle Schira (Frontiers in Education, 2023)
This paper focuses on new data collection methods made possible through first person-perspective or point-of-view (POV) recording technology and how these tools can provide important insights into students’ digital making and learning processes. Observation is a powerful tool, but researchers and educators are limited in what they can observe during a given moment and their inferences about student learning are made through the lens of an “outsider”. Audiovisual recording can supplement classroom observations to provide a more complete picture of students’ learning, but we contend that commonly-used methods are insufficient to capture the dynamic, social processes and literacies at play in a maker-oriented classroom. Through analyses of students’ learning during a digital tutorial-making task, we examine the affordances of and considerations for using POV “spyglasses” in digital literacies research. Spyglasses look and feel like regular glasses that one would wear to improve their vision, augmented with an integrated video camera and recording functionality. Our findings indicate that using tools that allow data to be collected from the student perspective gives access to important, alternate narratives about what students’ final products might show or represent about their digital skills and competencies. We also explore the important technical, ethical and data management considerations associated with using spyglasses as a data collection tool. As physical and digital making practices become more prominent in education and classroom-based research, this study highlights the importance of research tools capable of capturing the nuance and process of learning through making. Future research could explore the gap between researcher interpretation of collected data when it is not “read” alongside, or compared against, documentation from the “insider” perspective.